An Atomistic View on the Mechanism of Diatom Peptide‐Guided Biomimetic Silica Formation - Fanny Kozak; Dörte Brandis; Christopher Pötzl; Ludovica M. Epasto; Daniela Reichinger; Dominik Obrist; Herwig Peterlik; Anton Polyansky; Bojan Zagrovic; Fabian Daus; Armin Geyer; Christian FW Becker; et al. (Advanced Science, 2024)
Abstract Deciphering nature's remarkable way of encoding functions in its biominerals holds the potential to enable the rational development of nature‐inspired materials with tailored properties. However, the complex processes that convert solution‐state precursors into solid biomaterials remain largely unknown. In this study, an unconventional approach is presented to characterize these precursors for the diatom‐derived peptides R5 and synthetic Silaffin‐1A1 (synSil‐1A1). These molecules can form defined supramolecular assemblies in solution, which act as templates for solid silica structures. Using a tailored structural biology toolbox, the structure‐function relationships of these self‐assemblies are unveiled. NMR‐derived constraints are employed to enable a recently developed fractal‐cluster formalism and then reveal the architecture of the peptide assemblies in atomistic detail. Finally, by monitoring the self‐assembly activities during silica formation at simultaneous high temporal and residue resolution using real‐time spectroscopy, the mechanism is elucidated underlying template‐driven silica formation. Thus, it is demonstrated how to exercise morphology control over bioinorganic solids by manipulating the template architectures. It is found that the morphology of the templates is translated into the shape of bioinorganic particles via a mechanism that includes silica nucleation on the solution‐state complexes’ surfaces followed by complete surface coating and particle precipitation.